Development of a Portable SOFC System with Internal Partial Oxidation Reforming of Butane and Steam Reforming of Ethanol. (31st August 2017) - Sumi, Hirofumi; Yamaguchi, Toshiaki; Shimada, Hiroyuki; Fujishiro, Yoshinobu; Awano, Masanobu
Abstract : Internal partial oxidation reforming of butane and steam reforming of ethanol were investigated using microtubular solid oxide fuel cells (SOFCs) supported on nickel-gadolinia doped ceria (Ni-GDC) anode for portable power sources in an emergency situation and mobilities such as vehicles, robots and drones. At oxygen/carbon (O/C) ratio of 1.0, the Ni-GDC anode deteriorated for 28 h by internal partial oxidation of butane at 650 o C. Furthermore, power generation was also impossible after 8 and 79 h at steam/carbon (S/C) ratios of 1.0 and 1.5, respectively, by internal steam reforming of ethanol. Power can be generated over a period of more than 100 h at O/C = 1.5 in butane and at S/C = 2.0 in ethanol. We successfully demonstrated a prototype 100 W-scale portable SOFC system fueled by liquefied petroleum gas (LPG).